Hyperthermia in the treatment of cancer. - Bleehen, N. M. (Nature Publishing Group, 1982)
The clinical use of hyperthermia for the treatment of cancer continues to be hampered by technical difficulties. Current methods of local heating do not give satisfactory heat profiles. The biological concepts behind the potentially successful use of this treatment modality are discussed together with a review of the advantages and disadvantages of the various techniques employed. Some clinical studies using microwaves and radiofrequency heating are reviewed.